Convenient Synthesis of N-Tosyl-2-(difluoromethyl)aziridine and Its Application to the Preparation of Difluoromethyl-β-tryptamine Analogues - Kurosato, Fumihiro; Ishikawa, Takuya; Yamada, Yasunori; Hanamoto, Takeshi (Synlett, 2015)
N-Tosyl-2-(difluoromethyl)aziridine was easily prepared from p-toluenesulfonamide (TsNH2) and β-(difluoromethyl) vinyl sulfonium salt in excellent yield. The reaction of the aziridine and a wide range of indoles in the presence of Et2Zn proceeded smoothly to give the corresponding difluoromethyl-β-tryptamine analogues in good to excellent yields and with excellent regioselectivity.
Keywords: organofluorine; aziridine; ring-opening; indole; tryptamine